Large-area large-grain CsPbCl3 perovskite films by confined re-growth for violet photodetectors. (13th August 2022) - Guo, Tong; Zhao, Shiqi; Chu, Zihao; Ma, Jingli; Xu, Wanjin; Li, Yanping; Shi, Zhifeng; Ran, Guangzhao
Abstract: CsPbCl3 perovskite is an attractive semiconductor material with characteristics such as a wide bandgap, high chemical stability, and excellent optoelectronic properties, which broaden its application prospects for ultraviolet (UV) and violet photodetectors (PDs). However, large-area CsPbCl3 films with high coverage, large grains, and controllable thickness are still difficult to prepare by using the solution method due to the extremely low solubility of their precursors in conventional solvents. Herein, a water-assisted confined re-growth method is developed, and a CsPbCl3 microcrystalline film with an area of 3 cm × 3 cm is grown, the thickness of which is controllable within a range of several microns. The as-prepared thin film exhibits a flat and smooth surface, large grains, and enhanced photoluminescence. Furthermore, the fabricated violet PDs based on the prepared CsPbCl3 film show a high responsivity of 2.17 A W −1, external quantum efficiency of 664%, on/off ratio of 2.58 × 10 3, and good stability. This study provides a prospective solution for the growth of large-area, large-grain, and surface-smooth CsPbCl3 films for high-performance UV and violet PDs.